The October 2008 Nový Kostel earthquake swarm and its gas geochemical precursor. Issue 5 (2nd August 2016) - Weinlich, F. H.; Gaždová, R.; Teschner, M.; Poggenburg, J.
Abstract: A gas geochemical precursor anomaly was identified prior to the October 2008 Nový Kostel (Czech Republic) earthquake swarm with a peak magnitude ML of 3.8. This anomaly was observed as a deviation of CO2 concentrations from the long‐term annual CO2 concentration trend in the gas extracted from the scree at the Nový Kostel and Oldřišská gas monitoring stations, which are directly above the Plesná valley‐Počátky and Mariánské Lázně fault systems. Both sites are located within the major focal zone of the NW Bohemian swarm earthquake region at the northern edge of the Cheb Basin. A decrease in CO2 concentration started at Nový Kostel in September 2008, 17 days before the swarm, opposite to the usually increasing annual trend in the autumn period, and ended with a nearly coseismic drop immediately prior to the onset of the first swarm. The CO2 concentrations at Oldřišská, deviating from the annual trend, did not further increase after August 2008. The calculated horizontal strain field, based on the data of two permanent Global Navigation Satellite Systems stations, proved there was horizontal compression in this period. The increasing compression along the Plesná valley‐Počátky and Mariánské Lázně fault systems during the stress build‐up reduced the fault permeability prior to this earthquake swarm as indicated by the decrease in CO2 concentration. The 17‐day duration of the earthquake precursor at Nový Kostel and about 65 days at Oldřišská lie within the range of the precursor times that are hypothesized worldwide for an ML  = 3.8 earthquake. The nature of earthquake precursors and their origin are discussed, for example, as an indication of changed fault permeability by stress build‐up in the case of the Nový Kostel swarm earthquake precursor or as fault opening in other cases. Abstract : A gas geochemical precursor was identified in the gas directly above the Plesná valley‐Počátky fault systems prior to the October 2008 Nový Kostel, Czech Republic, earthquake swarm (peak magnitude ML = 3.8). It was observed as a deviation of CO2 concentrations from the annual CO2 concentration trend. CO2 concentration started decreasing 17 days before the swarm, matching the hypothesised duration of a precursor for an ML = 3.8 earthquake. The strain field provided evidence of horizontal compression during this period.